Policy and regulation as enablers for early childhood development centres in townships and informal settlements - Thoka, Boitumelo (University of Pretoria, 2020)
South Africa’s integrated policy on early childhood development makes provision for access to and delivery of equitable services to all children in South Africa. In his 2019 State of the Nation Address, President Cyril Ramaphosa emphasised the importance of early childhood development (ECD) in the development of South Africa’s human capital. ECD centres in South Africa are faced with various financial and human resources challenges preventing them from registering with the Department of Social Development and accessing the per-child subsidy. Regulations governing ECD centres have been found to be lacking in support of social entrepreneurs operating in resources deprived areas such as informal settlements and townships, areas challenged by poverty and unemployment. Policies and regulations that cater to the social entrepreneurial context of operations have been found to be effective in addressing challenges related to the provisioning of social entrepreneurship related services. This study contributes to literature with respect to challenges facing ECD centres in informal settlements and townships and the literature on how government can use policy and regulation to remedy for challenges experienced by ECD centres operating in informal settlements and townships. === Mini Dissertation (MBA)--University of Pretoria, 2020. === Gordon Institute of Business Science (GIBS) === MBA === Unrestricted